Particleboards from peanut-shell flour - Batalla, Leonel (2005)
Peanuts have been cultivated worldwide for hundreds, if not thousands, of years. However, most peanuts are sold without the shell, and so large quantities of peanut shells remain as byproducts in the field, not being used properly. In this work, the feasibility of making particleboard from milled peanut shells was studied. To obtain medium-density panels, a low compaction pressure and a high fiber content were used. The physical and mechanical properties of the panels were similar to those reported for wood-based particleboard when 80 wt % filler was used. The void content of the panels was experimentally deter mined and used in an attempt to predict the mechanical response of the panels. The stiffness of the particleboard could be greatly improved by a reduction of the porosity, but even a low void content had a critical effect on the strength of the composites. The stiffness of the composites could only be reasonably represented with simple theoretical models when the effect of the porosity was incorporated.